2001
DOI: 10.1051/apido:2001101
|View full text |Cite
|
Sign up to set email alerts
|

A scientific note on long-term stability of a home-made oxalic acid water sugar solution for controlling varroosis

Abstract: Since the work by Radetzski et al. (1994) on the use of oxalic acid for controlling varroosis, several reports have been published proving the efficacy and tolerability of this organic acid when applied to honeybees (Apis mellifera L.) by spraying or trickling. Tests were carried out by spraying water-diluted oxalic acid (Nanetti et al., 1995) or trickling a solution of oxalic acid, water and sugar (Imdorf et al., 1997;Mutinelli et al., 1997;Nanetti and Stradi, 1997) into colonies during broodless periods. Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Three different oxalic acid concentrations (4.2%, 3.2%, and 2.1%) mixed with sugar syrup were applied as treatments. To attain 4.2%, 3.2%, and 2.1% oxalic acid solutions, 100, 75, and 50 g of oxalic acid dehydrate was mixed with 1 L of sugar water (1:1) [43]. Treatments were applied only to frame spaces that contained bees.…”
Section: Oxalic Acid (Analar)mentioning
confidence: 99%
“…Three different oxalic acid concentrations (4.2%, 3.2%, and 2.1%) mixed with sugar syrup were applied as treatments. To attain 4.2%, 3.2%, and 2.1% oxalic acid solutions, 100, 75, and 50 g of oxalic acid dehydrate was mixed with 1 L of sugar water (1:1) [43]. Treatments were applied only to frame spaces that contained bees.…”
Section: Oxalic Acid (Analar)mentioning
confidence: 99%
“…For these reasons, the study of chemical compounds with miticidal characteristics has become relevant, particularly those chemical compounds normally found in hives or essential oils, such as oxalic acid (OA) (Prandin et al, 2001;Gregorc and Planinc, 2001;Marcangeli et al, 2003, Nanetti et al, 2003Marinelli et al, 2006; SCIENTIFIC NOTE B Rademacher and Harz, 2006;Bacandritsos et al, 2007), formic acid (Calderone, 2000;Bogdanov et al, 2002;Eguaras et al, 2003), and thymol (Imdorf et al, 1995). This type of compounds do not pollute a hive's products (Bogdanov et al, 2002) or produce resistant V. destructor strains.…”
mentioning
confidence: 99%
“…This type of compounds do not pollute a hive's products (Bogdanov et al, 2002) or produce resistant V. destructor strains. As a result, OA is one of the chemicals most often used as a complementary miticide (Prandin et al, 2001;Gregorc and Planinc, 2001;Nanetti et al, 2003;Marcangeli et al, 2003, Marcangeli andGarcía, 2004;Marinelli et al, 2006;Rademacher and Harz, 2006;Bacandritsos et al, 2007). Nevertheless, although some studies have reported the toxic activity of OA against V. destructor, few have examined its toxic effect on honeybees (Gregorc and Planinc, 2002) because it is normally assumed that the doses used are of low toxicity (Marcangeli et al, 2003;Marcangeli and García, 2004).…”
mentioning
confidence: 99%